QORAQALPOG‘ISTON RESPUBLIKASIDA MAKTABGAChA TA’LIM TIZIMINING TAShKILLAShTIRILIShI VA HUDUDIY JOYLAShUVIDAGI TAFOVUTLAR - Uzakbaev, K.K. (SCIENCE and SOCIETY, 2025)
The article describes the organization and distribution of the preschool education system in the Republic of Karakalpakstan.